Enhancing patient-engaged teamwork in healthcare: an observational case study. Issue 1 (January 2015) - Casimiro, Lynn M.; Hall, Pippa; Kuziemsky, Craig; O'Connor, Maureen; Varpio, Lara
Abstract The purpose of this study was to describe how teamwork that effectively engaged patients and families, manifested itself in an acute rural care setting in order to inform the development of teamwork skills. One hundred and forty participants were included in the study representing providers, patients, family, hospital and clinical support personnel, education specialists and students. Using a modified grounded theory approach, and informed by activity theory, observational field notes and interview transcripts were analyzed. Through the analysis of 343 events of providers interacting with, or exchanging information about, patients, three patterns of teamwork emerged that facilitated patient-engaged care: uniprofessional, multiprofessional and interprofessional. The data indicated that providers navigated between these patterns, as well as others, throughout their workday. Providers should be skilled in applying the construct of situation awareness in order to adopt a pattern of teamwork that best facilitates patient-engaged care. Interventions that can enhance teamwork should focus on: valuing the perspectives of others; developing relational competence and resilience; employing reflective learning and shared decision-making skills; and incorporating principles of change theory for both individuals and systems.